2018
DOI: 10.2147/ijn.s175425
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of deformable nanovesicles based on insulin-phospholipid complex for enhancing buccal delivery of insulin

Abstract: BackgroundNon-injectable delivery of peptides and proteins are not feasible due to its large molecular, high hydrophilic and gastrointestinal degradation. Therefore, proposing a new method to solve this problem is a burning issue.PurposeThe objective of this study was to propose a novel protein delivery strategy to vanquish the poor efficacy of buccal mucosa delivery systems for protein delivery and then investigate the detailed mechanisms of the enhanced buccal delivery of protein, using insulin as a model dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 30 publications
2
21
0
Order By: Relevance
“…Similar differences in the interaction of the mucosa with nanoparticles of opposite charges were observed by Chaves et al (2017). However, other studies have reported that cationic nanoparticles interacted more with the mucus and exhibited lower mucosal permeability in comparison to anionic nanoparticles (Chen et al, 2010; Yuan et al, 2011; Mouftah et al, 2016; Patil and Devarajan, 2016; Xu et al, 2018). This is also supported by studies in the lower gastrointestinal tract, whereby electrostatic interaction between cationic nanoparticles and the negatively charged mucins impeded the transport of the nanoparticles through the mucus layer (Hua et al, 2015).…”
Section: Nanoparticulate Drug Delivery Approachessupporting
confidence: 70%
See 1 more Smart Citation
“…Similar differences in the interaction of the mucosa with nanoparticles of opposite charges were observed by Chaves et al (2017). However, other studies have reported that cationic nanoparticles interacted more with the mucus and exhibited lower mucosal permeability in comparison to anionic nanoparticles (Chen et al, 2010; Yuan et al, 2011; Mouftah et al, 2016; Patil and Devarajan, 2016; Xu et al, 2018). This is also supported by studies in the lower gastrointestinal tract, whereby electrostatic interaction between cationic nanoparticles and the negatively charged mucins impeded the transport of the nanoparticles through the mucus layer (Hua et al, 2015).…”
Section: Nanoparticulate Drug Delivery Approachessupporting
confidence: 70%
“…Firstly, the physicochemical properties of the nanoparticles themselves (e.g., size, charge, composition, and surface properties) for optimal interaction with the sublingual or buccal mucosa. A number of different nanoparticulate systems have been evaluated for sublingual and buccal drug delivery, with polymer-based and lipid-based compositions being the most common (He et al, 2009; Roblegg et al, 2012; Teubl et al, 2013; Teubl et al, 2015; Mouftah et al, 2016; Patil and Devarajan, 2016; Chaves et al, 2017; Xu et al, 2018). The composition and structure of nanoparticles can be designed to confer a number of different properties, including mucoadhesion, bioadhesion, mucus-penetration, controlled release, and deformability (Hua et al, 2015).…”
Section: Nanoparticulate Drug Delivery Approachesmentioning
confidence: 99%
“…The particle sizes were 82.55 ± 3.85 nm with a narrow size distribution indicated by PDI < 0.200. The entrapment efficiency and deformability index of IPC-DNVs were 79.29% ± 2.41% and 38.25 ± 1.38 g/cm 2 /s ( n = 3) before lyophilization, respectively [29]. TEM micrographs of IPC-DNVs confirmed their spherical shape and whorl-like structure (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…IPC-DNVs were prepared using a thin-film hydration method, as described in our previous studies [28,29]. Briefly, 60 mg insulin and 600 mg phospholipid were independently dissolved in 6mL 0.1% trifluoroacetic acid–methanol and 60 mL dichloromethane, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…A J o u r n a l P r e -p r o o f mean particle size of 148 nm, zeta potential of 15.5 mV, PdI of 0.26 and an association efficiency of 97.56% were observed. Insulin was also conjugated with phosphate and encapsulated in flexible nanovesicles for buccal drug delivery by Xu et al [64]. The formulation had a mean particle size of 85.84 ± 2.38 nm and a zeta potential -26.2 ± 0.5 mV, and the deformability was also assessed.…”
Section: Recent Studies Carried Out By Mahdizadeh Barzoki Et Al Propmentioning
confidence: 99%